2021
DOI: 10.15252/embj.2021108130
|View full text |Cite
|
Sign up to set email alerts
|

ATP and cancer immunosurveillance

Abstract: While intracellular adenosine triphosphate (ATP) occupies a key position in the bioenergetic metabolism of all the cellular compartments that form the tumor microenvironment (TME), extracellular ATP operates as a potent signal transducer. The net effects of purinergic signaling on the biology of the TME depend not only on the specific receptors and cell types involved, but also on the activation status of cis‐ and trans‐regulatory circuitries. As an additional layer of complexity, extracellular ATP is rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(89 citation statements)
references
References 223 publications
(288 reference statements)
0
89
0
Order By: Relevance
“…The observation that certain cancer types or cancer subtypes metastasise to specific locations, a fact that cannot be solely be explained by circulation patterns, further reinforces the idea that tumours require particular environments for their growth and survival, even in later stages of cancer evolution (Nguyen et al , 2009). These are only but a few examples of how the TME can affect cancer initiation and evolution, as this topic is amply discussed in other reviews of this series (see Kepp et al , 2021; Parker et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The observation that certain cancer types or cancer subtypes metastasise to specific locations, a fact that cannot be solely be explained by circulation patterns, further reinforces the idea that tumours require particular environments for their growth and survival, even in later stages of cancer evolution (Nguyen et al , 2009). These are only but a few examples of how the TME can affect cancer initiation and evolution, as this topic is amply discussed in other reviews of this series (see Kepp et al , 2021; Parker et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more in-depth study of the regulatory processes of nucleotide metabolism has important theoretical and clinical significance. Moreover, recent studies have shown that abnormal nucleotide metabolism not only accelerates the development of tumors but also alters the normal immune response in the tumor microenvironment (TME), indicating the potential effectiveness of targeting nucleotide metabolism to enhance immunotherapy [ 5 7 ]. This review provides an overview of nucleotide metabolism and its role in cancer and emphasizes that nucleotide metabolism is a therapeutic target not only for chemotherapy but also for enhancing the efficacy of cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 190 , 191 Since this first report on ICD, multiple cancer treatment modalities have been reported to be endowed with such propensity. 192 , 193 They include additional chemotherapeutics (e.g. cyclophosphamide and oxaliplatin), certain physical cues (e.g.…”
Section: Icd-inducing Synthetic Agentsmentioning
confidence: 99%